Drosophila cytokine GBP2 exerts immune responses and regulates GBP1 expression through GPCR receptor Mthl10. - Ono, M.; Matsumura, T.; Sung, E.J.; Koyama, T.; Ochiai, M.; Shears, S.B.; Hayakawa, Y. (Insect Biochemistry and Molecular Biology, 2024)
Growth-blocking peptide (GBP), an insect cytokine, was first found in armyworm Mythimna separata. A functional analogue of GBP, stress-responsive peptide (SRP), was also identified in the same species. SRP gene expression has been demonstrated to be enhanced by GBP, indicating that both cytokines are organized within a hierarchical regulatory network. Although GBP1 (CG15917) and GBP2 (CG11395) have been identified in Drosophila melanogaster, immunological functions have only been characterized for GBP1. It is expected that the biological responses of two structurally similar peptides should be coordinated, but there is little information on this topic. Here, we demonstrate that GBP2 replicates the GBP1-mediated cellular immune response from Drosophila S2 cells. Moreover, the GBP2-induced response was silenced by pre-treatment with dsRNA targeting the GBP receptor gene, Mthl10. Furthermore, treatment of S2 cells with GBP2 enhanced GBP1 expression levels, but GBP1 did not affect GBP2 expression. GBP2 derived enhancement of GBP1 expression was not observed in the presence of GBP1, indicating that GBP2 is an upstream expressional regulator of a GBP1/GBP2 cytokine network. GBP2-induced enhancement of GBP1 expression was not observed in Mthl10 knockdown cells. Enhancement of GBP2 expression was observed in both Drosophila larvae and S2 cells under heat stress conditions; expressional enhancement of both GBP1 and GBP2 was eliminated in Mthl10 knockdown cells and larvae. Finally, Ca[2+] mobilization assay in GCaMP3-expressing S2 cells demonstrated that GBP2 mobilizes Ca[2+] upstream of Mthl10. Our finding revealed that Drosophila GBP1 and GBP2 control immune responses as well as their own expression levels through a hierarchical cytokine network, indicating that Drosophila GBP1/GBP2 system can be a simple model that is useful to investigate the detailed regulatory mechanism of related cytokine complexes.